Simultaneous oxidative determination of antibacterial drugs in aqueous solutions using an electrode modified with MWCNTs decorated with Fe3O4 nanoparticles - Bhengo, T.; Moyo, M.; Shumba, M.; Okonkwo, O. J. (Royal Society of Chemistry, 2021)
The present study describes a simple sensor developed from Fe3O4 and MWCNT nanoparticles for the simultaneous detection of sulfamethoxazole (SMX) and trimethoprim (TMP). Determination was carried out using cyclic voltammetry, electrochemical impedance spectroscopy, chronoamperometry and differential pulse voltammetry. Oxidation peaks were obtained at 910 mV (SMX) and 1120 mV (TMP) in Britton–Robinson buffer (pH 6.0). LODs of 1.10 × 10−8 M (SMX; 2.79 μg L−1) and 2.10 × 10−8 M (TMP; 6.10 μg L−1) were obtained. The Fe3O4/MWCNT/GCE showed good stability and selectivity. Furthermore, the simultaneous detection of SMX and TMP in tablets, urine and water was possible using the standard addition method.